2011
DOI: 10.1007/s11845-011-0762-9
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic outcomes in obese parturients: the effect of assessment in the high-risk clinic

Abstract: The outcomes of obese patients attending the anaesthetic clinic were mixed. Not all patients who were to advised have epidurals did so but those who did requested them in early labour and there was no requirement for general anaesthesia during emergency caesarean section and adverse airway events were avoided in this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Twelve studies with a total of 5678 patients were analysed the association between obesity and risk of Mallampati score ≥ 3 [ 7 , 14 , 23 , 24 , 26 , 28 34 ]. There were five case-control studies (two in the USA [ 23 , 28 ], one [ 27 ] in Germany, one in Denmark [ 35 ], and one in Ireland [ 32 ]) and 11 cohort studies (two in France [ 7 , 24 ], two in Turkey [ 25 , 31 ], one in Brazil [ 30 ], one in Israel [ 14 ], two in the USA [ 26 ], one in Greece [ 29 ] one in Italy [ 34 ] and one in the UK [ 33 ]). Two studies included parturients [ 25 , 31 ], and 14 recruited non-parturients [ 7 , 14 , 23 , 24 , 26 30 , 32 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies with a total of 5678 patients were analysed the association between obesity and risk of Mallampati score ≥ 3 [ 7 , 14 , 23 , 24 , 26 , 28 34 ]. There were five case-control studies (two in the USA [ 23 , 28 ], one [ 27 ] in Germany, one in Denmark [ 35 ], and one in Ireland [ 32 ]) and 11 cohort studies (two in France [ 7 , 24 ], two in Turkey [ 25 , 31 ], one in Brazil [ 30 ], one in Israel [ 14 ], two in the USA [ 26 ], one in Greece [ 29 ] one in Italy [ 34 ] and one in the UK [ 33 ]). Two studies included parturients [ 25 , 31 ], and 14 recruited non-parturients [ 7 , 14 , 23 , 24 , 26 30 , 32 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were five case-control studies (two in the USA [ 23 , 28 ], one [ 27 ] in Germany, one in Denmark [ 35 ], and one in Ireland [ 32 ]) and 11 cohort studies (two in France [ 7 , 24 ], two in Turkey [ 25 , 31 ], one in Brazil [ 30 ], one in Israel [ 14 ], two in the USA [ 26 ], one in Greece [ 29 ] one in Italy [ 34 ] and one in the UK [ 33 ]). Two studies included parturients [ 25 , 31 ], and 14 recruited non-parturients [ 7 , 14 , 23 , 24 , 26 30 , 32 34 ]. Of the included studies, emergent tracheal intubation was used in two [ 23 , 25 ] and non-emergent tracheal intubation in the other 14 [ 7 , 14 , 24 , 26 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One London hospital reported that the indication for 26% of women presenting to their high-risk clinic was 'morbid obesity' 44 . Aslani et al demonstrated, in a cohort of 42 women with a mean BMI of 37.6 kg/m 2 (± 5.7), that those counselled to receive epidural analgesia requested it early in labour 45 . Those who subsequently required emergency caesarean section (n=5) successfully avoided general anaesthesia.…”
Section: The Antenatal Anaesthetic Consultationmentioning
confidence: 99%